Kaempferol attenuates nonalcoholic steatohepatitis by regulating serum and liver bile acid metabolism - Lu, Yifei; Shao, Mingmei; Zhang, Caiyun; Xiang, Hongjiao; Wang, Junmin; Wu, Tao; Ji, Guang (Frontiers in Pharmacology, 2022)
Objective: Changes in bile acids (BA) are increasingly recognized as potential targets for non-alcoholic steatohepatitis (NASH). Kaempferol has been proved to be anti-inflammatory and reduce the disorder of lipid metabolism. In order to analyze BA profile in NASH mice, and determine the predictive biomarkers of kaempferol treatment, a serum targeted metabolomics and liver tissue RNA sequence (RNA-seq) were carried out. Design:6 normal control mice (NC group), 8 HFD-fed mice (HFD group), 8 kaempferol-treated with HFD-fed mice (HFD+KP group) were included in the present study. Ultra-performance liquid chromatography coupled to tandem mass spectrometry system (UPLC-MS/MS) was used to quantify serum and liver BAs and RNA-seq was used to quantify liver differentially expressed genes related to BA metabolism. Results: The serum levels of CA, βMCA, UDCA and 12-DHCA as well as ωMCA both in serum and liver were significantly decreased in HFD group compare with NC group and kaempferol can increase the serum level of βMCA, UDCA and ωMCA and the liver level of 12-DHCA. The serum levels of TDCA, THDCA, TUDCA, TDCA/CA and TDCA/DCA was significantly increased in HFD group compare with NC group and kaempferol can decrease them. Furthermore, NASH mice had higher liver level of total CA%, total CDCA%, primary BAs/secondary BAs,12α-OH BAs/non-12α-OH BAs and conjugated BAs/unconjugated BAs and all decreased after kaempferol treatment. According to the RNA-seq results, we found that compared with the NC group, the mRNA expression of cholesterol-7α-hydroxylase (CYP7A1) in the HFD group was significantly increased, and the mRNA expression of sterol 12α‐hydroxylase (CYP8B1) and multidrug resistance-related protein 3 (MRP3) was significantly decreased, while kaempferol significantly promoted the mRNA expression of mitochondrial sterol 27-hydroxylase (CYP27A1) and Na+-taurocholate cotransporting polypeptide (NTCP). Conclusions: βMCA, CA, UDCA,12-DHCA, ωMCA, CDCA, TωMCA, TDCA, THDCA, TCDCA and TUDCA in serum, as well as 6,7-diketoLCA,12-DHCA and ωMCA in liver may be potential biomarkers for kaempferol to improve NASH. HFD-induced NASH may be associated with the increase of CYP7A1 and CYP8B1 leading to increased BA synthesis and the decrease of MRP3 leading to decreased BA synthesis, and kaempferol may alleviate NASH by increasing CYP27A1 and NTCP to enhance BA transport.